Effects of Evolocumab on the Postprandial Kinetics of Apo (Apolipoprotein) B100- and B48-Containing Lipoproteins in Subjects With Type 2 Diabetes. Issue 2 (February 2021) - Taskinen, Marja-Riitta; Björnson, Elias; Kahri, Juhani; Söderlund, Sanni; Matikainen, Niina; Porthan, Kimmo; Ainola, Mari; Hakkarainen, Antti; Lundbom, Nina; Fermanelli, Valentina; Fuchs, Johannes; Thorsell, Annika; et al.
Abstract : Objective: Increased risk of atherosclerotic cardiovascular disease in subjects with type 2 diabetes is linked to elevated levels of triglyceride-rich lipoproteins and their remnants. The metabolic effects of PCSK9 (proprotein convertase subtilisin/kexin 9) inhibitors on this dyslipidemia were investigated using stable-isotope-labeled tracers. Approach and Results: Triglyceride transport and the metabolism of apos (apolipoproteins) B48, B100, C-III, and E after a fat-rich meal were investigated before and on evolocumab treatment in 13 subjects with type 2 diabetes. Kinetic parameters were determined for the following: apoB48 in chylomicrons; triglyceride in VLDL1 (very low-density lipoprotein) and VLDL2 ; and apoB100 in VLDL1, VLDL2, IDL (intermediate-density lipoprotein), and LDL (low-density lipoprotein). Evolocumab did not alter the kinetics of apoB48 in chylomicrons or apoB100 or triglyceride in VLDL1 . In contrast, the fractional catabolic rates of VLDL2 -apoB100 and VLDL2 -triglyceride were both increased by about 45%, which led to a 28% fall in the VLDL2 plasma level. LDL-apoB100 was markedly reduced by evolocumab, which was linked to metabolic heterogeneity in this fraction. Evolocumab increased clearance of the more rapidly metabolized LDL by 61% and decreased production of the more slowly cleared LDL by 75%. ApoC-III kinetics were not altered by evolocumab, but the apoE fractional catabolic rates increased by 45% and the apoE plasma level fell by 33%. The apoE fractional catabolic rates was associated with the decrease in VLDL2 - and IDL-apoB100 concentrations. Conclusions: Evolocumab had only minor effects on lipoproteins that are involved in triglyceride transport (chylomicrons and VLDL1 ) but, in contrast, had a profound impact on lipoproteins that carry cholesterol (VLDL2, IDL, LDL). Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02948777. Abstract : Supplemental Digital Content is available in the text.